2019
DOI: 10.3390/foods8100454
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Candida pyralidae and Pichia kluyveri to Control Spoilage Microorganisms of Raw Fruits Used for Beverage Production

Abstract: Undesired fermentation of fruit-derived beverages by fungal, yeast and bacterial spoilage organisms are among the major contributors of product losses in the food industry. As an alternative to chemical preservatives, the use of Candida pyralidae and Pichia kluyveri was assessed for antimicrobial activity against several yeasts (Dekkera bruxellensis, Dekkera anomala, Zygosaccharomyces bailii) and fungi (Botrytis cinerea, Colletotrichum acutatum and Rhizopus stolonifer) associated with spoilage of fruit and fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…24 In contrast to our findings, Fiori et al 32 reported a significant inhibition of A. carbonarius infection on grape berries by living yeast cells, whereas no such effects were observed using yeast VOCs. Mewa-Ngongang et al 33 in a similar study reported the protective role of two antagonistic yeasts (Candida pyralidaeand Pichia kluyveri) against the growth of pathogenic fungi on apples and grapes. The inhibitory activity of yeast strains was characterized by a blend of VOCs having organic acids, alcohols, and esters.…”
Section: Resultsmentioning
confidence: 96%
“…24 In contrast to our findings, Fiori et al 32 reported a significant inhibition of A. carbonarius infection on grape berries by living yeast cells, whereas no such effects were observed using yeast VOCs. Mewa-Ngongang et al 33 in a similar study reported the protective role of two antagonistic yeasts (Candida pyralidaeand Pichia kluyveri) against the growth of pathogenic fungi on apples and grapes. The inhibitory activity of yeast strains was characterized by a blend of VOCs having organic acids, alcohols, and esters.…”
Section: Resultsmentioning
confidence: 96%
“…One out of 20 jars infected with B. cinerea in the curative treatment showed signs of spoiled berries (95% inhibition), while a 100% inhibition was observed for the curative treatments of M. laxa. This result is comparable to the 100% suppression of Aspergillus carbonarius, Colletotrichum acutatum, and Rhizopus stolonifer growth on grapes by Candida zemplinina, Candida pyralidae, Saccharomyces cerevisiae, and P. kluyveri [Fiori et al, 2014;Mewa--Ngongang et al, 2019b;Zhu et al, 2015]. Although preventive results were notable, curative biocontrol applications resulted in substandard grape colour and texture, although spoilage was vastly minimised.…”
Section: Preventive and Curative Treatments: Table Grape Bioassaymentioning
confidence: 67%
“…Several authors have highlighted the importance of non--Saccharomyces yeasts in addressing food spoilage [Mewa-Ngongang et al, 2017, 2019bOro et al, 2014]. Their widespread use in the food industry, their ability to handle and grow quicker than spoilage organisms, and their ability to produce killer toxins have been widely acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…(Nees), and Rhizoctonia sp. (Kühn) [ 40 , 41 ]. The yeasts which exert biocontrol activity against these fungi are Trichoderma harzianum (Rifai), Pichia membranifaciens (E.C.…”
Section: Yeast Applications Against Pathogenic Fungi Of the Grape In Post-harvestmentioning
confidence: 99%
“…carpophila Phaff & M.W. Miller (1961)), Cryptococcus laurentii ((Kufferath) CE Skinner), Cryptococcus flavus , Cryptococcus albicus , Candida pyralidae (Kurtzman (2001b)), Pichia kluyveri (Bedford ex Kudryavtsev (1960)), and P. expansum [ 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Yeast Applications Against Pathogenic Fungi Of the Grape In Post-harvestmentioning
confidence: 99%